The Impact Of Corporate Moral Hazard On Esg Performance Of The U.S. Mncs: The Interaction Effect Of Type Of Ownership - El Shlmani, Zahra Mohamed Abdulsalam (2024)
This study analyzes the impact of corporate moral hazard on ESG performance. The study also investigates the interaction effect of the ownership structure on the relationship between corporate moral hazard _ expressed in the gross value and volume of corporate enforcement actions _ and ESG performance.